Fandom nationalism in China: the effects of idol adoration and online fan community engagement. Issue 4 (2nd October 2022) - Liao, Xining; Koo, Alex Zhi-Xiong; Rojas, Hernando
Abstract: While many fandom activism studies see fans as a potential force to challenge the existing political order, participants of fan groups in China have been transformed into nationalists and government supporters. Utilizing online survey data collected in 2020, we established an initial statistical model to test the mobilizing mechanisms underlying Chinese fandom nationalism. Our findings suggest that, among individuals who participate in online fan communities, stronger affection toward idols is associated with stronger nationalist sentiments and eventually leads to more frequent online pro-government expression. However, among individuals who do not engage with online fan communities, such indirect effects are non-significant. Our findings further show that online fan communities (饭圈) play a significant role in mobilizing fandom nationalism in China.